If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -4b = 14 Solving 3a + -4b = 14 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4b' to each side of the equation. 3a + -4b + 4b = 14 + 4b Combine like terms: -4b + 4b = 0 3a + 0 = 14 + 4b 3a = 14 + 4b Divide each side by '3'. a = 4.666666667 + 1.333333333b Simplifying a = 4.666666667 + 1.333333333b
| 2sinX+X=0 | | sinx+x=0 | | 6/2/3=18/N | | 830+840+380+380= | | 3/8m=9 | | 13.95x+8=15.95x | | D=175+70t | | D=175+70 | | D=175+-70 | | -9(t+4)=36 | | 27+3y-6=11y-9-2y | | D=175+-70t | | x+18+4x=-30-4x-33 | | 24y=14y-8 | | 4r^6+15r^3-25=0 | | 14q^2-33qb+18b^2=0 | | -3(x-1)+8(x-3)=6x+7+-5x | | 50a^4+60a^2-20=0 | | 5a^4+6a^2-2=0 | | -7r+3t-8s-5r+12s+14r+5s-11r= | | 2s^2-7s-4=0 | | (u-3)(u-3)=2u^2-15u+29 | | 15a^2+17a-42=0 | | (-5)2= | | -15a^2-17a+42=0 | | 2x(3+6)=15 | | 3/x+2-1/x=1/5x | | 2+13x+15x^2=0 | | 6(9)+3(3)-1= | | 45x^2+39x+6=0 | | 3(4)+2(2)-4= | | 4(16)+5(-4)-2= |